The effect of the fair inquiry model on achievement by bringing about the dialectical development of literary fifth-grade students in history subject - Ibrahim Mohamed, Hanaa (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to find out the impact of the fair survey model in achievement and the development of dialectic thinking among fifth-grade literary students in the subject of history